The Implementation of a Gamification Approach to Enhance Learning Motivation Among Generation Z Students in History Courses - Megiridha Lopes; Muhammad Aqil (Council: Education Journal of Social Studies, 2026)
The rapid development of digital technology has transformed the learning characteristics of Generation Z students, who tend to prefer interactive, collaborative, and experiential learning environments. However, history instruction in higher education is still largely dominated by conventional teaching approaches, resulting in low student learning motivation. This study aims to describe the implementation of a gamification approach in a history course and to analyze its role in enhancing the learning motivation of Generation Z students. The study employed a descriptive qualitative approach conducted in the History Education Study Program. Data were collected through classroom observations, in-depth interviews, and documentation, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which consists of data condensation, data display, and conclusion drawing and verification. The findings indicate that the implementation of gamification through the use of points, leaderboards, challenges, and rewards successfully increased students' enthusiasm, active participation, learning readiness, and engagement throughout the learning process. Interview results further revealed that gamification created a more engaging learning environment, enhanced students' learning motivation, and encouraged them to participate more actively in discussions, collaborate with peers, and prepare course materials before class. Furthermore, the gamification approach transformed the instructional process from teacher-centered learning to student-centered learning, enabling students to play a more active role in constructing knowledge. This study confirms that gamification is an effective instructional strategy for enhancing learning motivation while fostering more interactive, meaningful, and engaging history learning experiences that align with the characteristics of Generation Z students.